Efektivitas Model Project Based Learning Pada Mata Pelajaran Pendidikan Agama Kristen Terhadap Minat Belajar Peserta Didik di SMA Negeri 39 Jakarta - Nainggolan, Fitri Oktaviana (Fakultas Ilmu Keguruan dan Pendidikan, Universitas Kristen Indonesia, 2025)
This study aims to determine the effectiveness of the Project Based Learning (PBL) model in improving students' interest in learning Christian Religious Education at SMA Negeri 39 Jakarta. Based on observations during the Field Experience Practice, it was found that student engagement and creative thinking abilities were still low. Some factors contributing to this include teaching methods that have not optimized student participation and creativity. This study aims to analyze the causes of students' lack of interest and find solutions to improve it. The theory used is Edgar Dale’s Cone of Experience, synchronized with Pestalozzi’s theory, which emphasizes the importance of real and spiritual experiences in teaching Christian Religious Education. The research method used is qualitative with a descriptive approach, gathering data from one teacher and nine students at SMA Negeri 39 Jakarta through observation, interviews, and documentation. The results showed that: (1) The previous teaching methods felt monotonous and did not provide real or spiritual experiences to students, (2) Project Based Learning is effective in enhancing student engagement by applying Pestalozzi’s theory on the importance of involving sensory experiences in learning, (3) The teaching model significantly influences students' interest in Christian Religious Education. Based on these findings, it can be concluded that Project Based Learning has great potential to improve students' interest in learning Christian Religious Education at SMA Negeri 39 Jakarta.